Directive Speech Acts in Aisha Saeed’s Novel Amal Unbound - Pertiwi Amarylis Duta (EDP Sciences, 2021)
Communication within society comprises diverse linguistic choices influenced by social interaction. This study discusses how structures of utterances and types of directive illocutionary acts pertain to the characters’ qualities and non-linguistic factors in Amal Unbound (2018) by Aisha Saeed. This analysis aims to find out the connection between utterances the characters’ qualities such as age, occupation, education, relationship, social status, and non-linguistic factor like the topic or purpose. The underlying theory used in this study is Bach and Harnish’s directive speech act categorization. This study was conducted using qualitative method since it involves discussion on linguistic data (words, phrases, sentences, and utterances). The result of the analysis shows that the utterances of the novel’s characters are affected by the quality they possess and surrounding non-linguistic factors. In conclusion, understanding illocutionary acts open our eyes of the significance of appropriate uses of language in social practice.